Barthes's "Musica Practica" and its Antecedents. (3rd July 2021) - Cheung Salisbury, Matthew
ABSTRACT: This article explores Roland Barthes's use of the term musica practica (which emanates from historical theoretical treatises on music) in his eponymous essay of 1970, which was originally a contribution to a journal issue dedicated to Ludwig van Beethoven. It is possible that Barthes was familiar with the term either from awareness of medieval music theory or through its secondary use by writers whose works he knew. It is suggested that the term may have been employed by Barthes as a result of dialogue with the composer André Boucourechliev, the editor of the Beethoven issue who later became Barthes's own piano teacher. Nevertheless, it appears to be used as a shorthand for the concept Barthes propounds in contemporaneous essays using the performance of music as an analogy, in other words for engaging with texts, like Beethoven's, that elicit active participation from the performer, allowing them to contribute to the formulation of a work's meaning.